Perception Analysis on Tax Audit Quality Jawa Barat I Regional Tax Office Analisis Persepsi Kualitas Pemeriksaan Pajak: Studi Kasus pada Kanwil DJP Jawa Barat I) - Ferry Irawan (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2016)
This paper tries to investigate the quality of tax audit in Directorate General of Taxes (DGT) especially in Jawa Barat I Regional Tax Office (Kanwil DJP Jawa Barat I). In this research, we used a descriptive and qualitative approach. Also, we conduct a deep interview with several key persons in each tax office and officials at DGT Head Office. It is found that the quality of tax audit can be categorizedd as “good”. However, it needs continuous improvement.